1888 Md. Code 1457 - (:unkn) unknown (My University, 1888)
Election Districts - Fences, § 99: Prohibited carrying, on days of an election , any gun, pistol, dirk, dirk-knife, razor, billy or bludgeon. Punishable by a fine of $5-20.
Keywords: CARRY - CERTAIN PUBLIC PLACES